Application of balanced scorecard as a measure of organizational performance in Turkish firms - Etisoy, Nihal (My University, 2005)
Bu tezin amacı, Türkiye'de Balanced Scorecard (Dengelenmiş Skor Kartı-Kurumsal Performans Karnesi) sistemini uygulayan firmaların özelliklerini ve bu stratejik yönetim, ölçüm ve iletişim aracını ne şekilde kullandıklarını araştırmak ve Balanced Scorecard uygulamasının başarısına etki eden faktörleri belirlemektir. Tezde öncelikle Balanced Scorecard sistemi hakkında genel bilgi içeren bir giriş yapılmıştır. Giriş bölümünü detaylı bir literatür taraması takip etmektedir. Literatür taraması sonucunda Balanced Scorecard uygulamasının başarısına etki eden faktörler belirlenmiştir. Bu faktörlere dayanarak anket soruları hazırlanmıştır. Bu anketin sonucunda, Türkiye'deki firmaların Balanced Scorecard uygulamalarındaki başarısının; çalışanların Balanced Scorecard geliştirme ve uygulamasına katılımı, Balanced Scorecard hakkında şirket içi iletişimin uygun olması ve Balanced Scorecard'ın geniş anlamda uygulanmadan önce pilot çalışma yapılarak denenmesi faktörlerine bağlı olduğu sonucu çıkmıştır. Anket, şirketlerde Balanced Scorecard Sistemi'nden sorumlu kişiler tarafından doldurulmuştur ve ankette onlara göre Balanced Scorecard uygulamasının başarısına etki eden faktörler de belirlenmiştir. Bu şekilde Türkiye'deki firmaların yakın gelecekte hangi faktörleri önemseyerek başarılarını arttırabilecekleri hakkında ipuçları elde edilmiştir. The aim of this thesis is to investigate the characteristics of Turkish companies that implement the Balanced Scorecard, to search thoroughly how these companies implement this strategic management, measurement and communication tool and to determine the factors that affect the successful implementation of Balanced Scorecard. In the thesis, firstly a general introduction to Balanced Scorecard system is done. A detailed literature survey follows the introduction part. With the literature review, factors that affect the successful implementation of Balanced Scorecard are obtained. A questionnaire is prepared by considering these factors. As a result of the questionnaire, it is found out that the success of Balanced Scorecard implementation in Turkish companies is related with the level of employee involvement to Balanced Scorecard preparation and implementation, appropriateness of the company-wide communication of Balanced Scorecard and implementation of a pilot Balanced Scorecard before broadening the Balanced Scorecard implementation. The questionnaires are answered by the responsible of Balanced Scorecard implementation in every company and the questionnaire has questions about their opinion about the importance of factors that affect the success of Balanced Scorecard. By this way, the factors that will be considered important for Balanced Scorecard implementations for Turkish companies in the near future are also obtained.
Keywords: Genel yönetim; Yönetim